Technologies for traceability, safety and control of pesticide residues in the food production chain of plant origin: a review study (Research, Society and Development, 2020)
The objective of this article was to carry out an integrative literature review on the aspects involved and the main traceability technologies aimed at the safety and control of pesticide residues in plant foods. The analysis of the articles occurred in a descriptive way, in order to present its most relevant aspects and gather knowledge produced on the topic. To this end, 67 articles published in the last ten years (2010 - 2020) in national and international journals were selected. The study made it possible to observe that the development of traceability technologies, supported especially in the use of the internet and artificial intelligence, presents itself as an important reinforcement in guaranteeing precision and safe flow of information in the food production chain. In addition, consumer demand for more transparency and security in the production chain and the establishment of international regulatory mechanisms for traceability under food commodities have driven the development of these technologies. However, most of the reviewed articles point out that such technologies are still very much associated with logistics processes, to the detriment of aspects related to food security and sanitary control over pesticide residues in plant foods.